DEIKSIS BAHASA BALI DIALEK BUGBUG KECAMATAN KARANGASEM (KAJIAN PRAGMATIK) - Ni Komang Aryani (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2020)
This research has three objectives, namely to describe the form of the person deixis, the form of the place deixis, and the form of the time deixis in Balinese, Bugbug dialect, Karangasem sub-district. This research is a qualitative descriptive research. The object of this research is the people’s utturance of the Bugbug village community with data and data sources in the form of speech or conversational dialogue that has been transcripted into text. Collecting data using utterances methods of simak bebas libat cakap. The interactive model data analysis is used as the data analysis in this research. The results showed that the deixis aspects contained in the utterances included a personal expression in the form of a single first person deixis, there were 6 forms. The first plural deixis has one form, the second deixis has 7 forms, the third deixis is single, there is one, third persona is plural has one form. Space deixis (place) has 13 forms and Deixis when there are 7 forms.